Saliva in the Diagnosis of COVID-19 - Elmas Pınar KAHRAMAN KILBAŞ (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2021)
The use of saliva samples for the diagnosis of severe acute respiratory syndrome-Coronavirus-2 (SARS-CoV-2) provides several advantages over the use of nasopharyngeal (NP) swabs, such as comfort, ease of self-collection, less use of personal protective equipment, and protection of healthcare personnel from transmission. This review included current studies using saliva samples for the detection of SARS-CoV-2, comparing its sensitivity, cycle threshold, and specificity with those of NP swab. In the literature, the sensitivity rates of saliva samples in the diagnosis of SARS-CoV-2 ranged from 70% to 98%. Despite different opinions, we concluded that saliva is a reliable sample for the detection of SARS-CoV-2. However, studies with large samples and comparing different diagnostic methods are needed to reach precise and reliable results and include saliva collection in diagnostic guidelines.